A (in)segurança privada em Portugal - Pereira, David Marcos Borralho (2015)
Along with the food and the comfort, safety has always been one of the human priorities. In pursuit of this objective, man developed self-preservation mechanisms, went to live in society and created rules to control the community life. In the West and in the late eighteenth century, with the creation of states as we know them today, the monopoly of security, among other powers, has been preserved untouched until the last quarter of this century. With the bankruptcy of the welfare state and the rise of the regulatory state, many of the essential tasks for the community have also been carried out by private companies or institutions, including education, health care and security. Although not easy, education and health care have been more opened to be managed by the private sector. Instead, the privatization of the security sector has seen much more resistance. Still, especially in the West, the states have delegated some of the security competences to private companies. Portugal is no exception to the rule and, after a few years of unregulated activity, in 1982 was published the first law regulating the private security. After the initial stages of development (evolution and maturation), which lasted until the early years of the 2000‘s, the private security now seems to have reached maturity. Today, now with a new legal system, composed by Law no. 34/2013, of 16 may, its regulations and complementary legislation, now private security encompasses other activities and competences - becoming, an increasingly complement to public safety. It has also increased the pre-requisites and control mechanisms for private security companies, and strengthened the rules that limit their scope of activity.